Sofosbuvir and ribavirin for 6 weeks is not effective among people with recent hepatitis C virus infection: The DARE‐C II study. Issue 6 (27th October 2016) - Martinello, Marianne; Gane, Edward; Hellard, Margaret; Sasadeusz, Joe; Shaw, David; Petoumenos, Kathy; Applegate, Tanya; Grebely, Jason; Maire, Laurence; Marks, Philippa; Dore, Gregory J.; Matthews, Gail V.
Abstract : While interferon‐based therapy has excellent efficacy in acute and recent hepatitis C virus (HCV) infection, the side effect profile limits implementation. Sofosbuvir and ribavirin for 12‐24 weeks is safe and well tolerated in chronic HCV, with efficacy dependent on genotype and disease stage. The aim of this study was to assess the efficacy of sofosbuvir and ribavirin for 6 weeks in individuals with recent HCV infection. In this open‐label study conducted in Australia and New Zealand, adults with recent HCV (duration of infection <12 months) received sofosbuvir 400 mg daily and weight‐based ribavirin (<75 kg, 1, 000 mg/day; ≥75 kg, 1, 200 mg/day) for 6 weeks. The primary efficacy endpoint was sustained virological response at posttreatment week 12 (SVR12). Nineteen participants commenced sofosbuvir and ribavirin (89% male, 74% with human immunodeficiency virus, 68% genotype 1a). Four (21%) reported a symptomatic HCV seroconversion illness, including 2 with jaundice. At baseline, median HCV RNA was 5.4 log10 IU/mL (interquartile range 4.4‐6.8) and median estimated duration of infection was 37 weeks (interquartile range 27‐41). At the end of treatment, HCV RNA was nonquantifiable in 89% (n = 17). SVR4 and SVR12 were 42% (n = 8) and 32% (n = 6), respectively. Treatment failure was due to nonresponse (n = 2), posttreatment relapse (n = 9), reinfection (n = 1), and loss to follow‐up (n = 1). The regimen was well tolerated with minimal hematological toxicity. SVR12 was related to baseline HCV RNA (≤6 log10 IU/mL, P = 0.018) and early on‐treatment viral kinetics (HCV RNA below the level of quantitation at week 1, P = 0.003). Conclusion : Six weeks of sofosbuvir and ribavirin was safe and well tolerated, but efficacy was suboptimal; further research is needed to determine whether more potent interferon‐free direct‐acting antiviral regimens will allow treatment duration to be shortened in recent, predominantly asymptomatic HCV infection. (Hepatology 2016;64:1911‐1921).